Are Nutritional Guidelines Followed in the Pediatric Intensive Care Unit? - Jouancastay, Mylène; Guillot, Camille; Machuron, François; Duhamel, Alain; Baudelet, Jean-Benoit; Leteurtre, Stéphane; Recher, Morgan (Frontiers in Pediatrics, 2021)
Background. French (2014) and American (2017) pediatric guidelines recommend starting enteral nutrition (EN) early in pediatric intensive care. The aim of this study was to compare the applicability of guidelines in the pediatric intensive care unit (PICU) and identify risk factors of no-application of the guidelines. Methods. This retrospective, single-center study was conducted in a medical-surgical PICU between 2014 and 2016. All patients from one month to 18 years old, with a length of stay >48 hours and an exclusive EN at least one day during the PICU stay were included. The outcome variable was application of the 2014 and 2017 guidelines, defined by energy intakes ≥ 90% of recommended intake at least one day as defined by both guidelines. Risk factors of no-application were studied comparing “optimal EN” versus “non-optimal EN” groups for both guidelines. Results. In total, 416 children were included (mortality rate 8%). Malnutrition occurred in 36% of cases. Mean energy intake was 34 ± 30.3 Kcal/kg/day. The 2014 and 2017 guidelines were applied in 183 (44%) and 296 (71%) patients, respectively (p<0.05). Following the 2017 guidelines, enteral energy intakes were considered as “satisfactory enteral intake” for 335 patients (81%). Hemodynamic failure was a risk factor of no-application of both guidelines (p=0.047). Conclusion: In our PICU, energy intake received approached the intake recommended by the American 2017 guidelines, which used the predictive Schofield equations and seem more useful and applicable than the higher recommendations of the 2014 guidelines. Multicenter studies to validate the pediatric guidelines seem necessary.